The Role of DPC ASPETRI Surabaya in Improving Community Health through the Distribution of Jamu at the Health Post in Joyoboyo Terminal - Wibowo, Teguh Setiawan; Wulansari, Christina; Hidayati, Nurul; Kholiq, Abdul (Westscience Press, 2025)
Public health is an important aspect in supporting daily activities, especially for public transport users and workers in terminal environments. Jamu, as a heritage of Indonesian herbal medicine, has great potential in boosting immunity and preventing various diseases. This community service activity was conducted by the Surabaya Branch of the Indonesian Traditional Herbal Healers Association (DPC ASPETRI) through the distribution of jamu at the Health Post in Joyoboyo Terminal. The primary aim of this activity is to raise public awareness of the benefits of jamu as part of a healthy lifestyle and to provide easy access to quality herbal drinks. This activity involved a brief education on the benefits of jamu, the proper consumption methods, and the distribution of jamu to the terminal community. The results of the activity showed a positive response from the public, with an increased understanding of jamu as an herbal alternative for maintaining health. It is hoped that this activity will serve as a model for similar initiatives in various places, supporting the preservation and utilization of jamu in the public health system.